(3eLeY GdHMQjf hedJbi GdfjQjfs - (3CMeO Hf Ydj Hf KYdH Hf GdSGYGJj GdHZOGOj , eXaQ GdOjf,J (B694 (3g` s ((3MSf GHf YhGV s)
(3ChdgG (B:s
(3GdMeO ddg LGYd GdYdeGA CfLekG ddEgJOGA CeG HYO agPG cJGH jUZQ ddMGaX MLeg jMhi eNJUQ GdTjN CHj GdMSf GdbOhQi hefXheI CHj MaU GdfSai hgYeG HMQGf RGNQGf hgPG eLeY GdHMQjf s
(3BNQgG (B:s
(3hNUhUkG ai LfGSGJg GdNWjI aEf GdEMJjGW ajgG MJe hGddg gh GdeTchQ Ydi EaGVg fYeg Je gPG GdeNJUQ HYhf Gddg hMSf GdJhajb s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B170 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B4 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B101s
Keywords: (3Gdabg GdESdGejs